Parietal dysfunction in children with prenatal alcohol exposure - Woods, Keri (Department of Human Biology, 2018)
The parietal lobe has been shown to be one of the regions most affected by prenatal alcohol exposure. Functional domains dependent on intact parietal functioning, including mathematical and visuospatial ability, have been consistently implicated in fetal alcohol spectrum disorders. This thesis examines, in children, using blood oxygenation level dependent (BOLD) functional Magnetic Resonance Imaging, the effect of prenatal alcohol exposure on brain activation during symbolic and nonsymbolic number processing, and place learning in a virtual environment. These functional domains were investigated using tasks of proximity judgment and exact addition to assess neural correlates of symbolic number processing in 65 children (mean age ± SD = 9.45 ± 0.42 years), nonsymbolic number comparison at varying difficulties in 34 children (11.55 ± 1.15 years), and place learning in a virtual reality computer generated (CG) arena in 57 children (9.44 ± 0.42 years; 29 boys). In the symbolic number processing tasks greater prenatal alcohol exposure was related to less activation in the right horizontal intraparietal sulcus known to mediate mental representation and manipulation of quantity. Children with fetal alcohol syndrome and partial fetal alcohol syndrome appeared to compensate for this deficit by increased activation of the left angular gyrus during the proximity judgment task. Syndromal children with fetal alcohol syndrome or partial fetal alcohol syndrome also demonstrated poor recruitment of the right horizontal intraparietal sulcus during nonsymbolic number comparison, indicating that mental representation and manipulation of quantity are impaired in children with heavy prenatal alcohol exposure, irrespective of the representation format used. This impairment was compensated for by the left angular gyrus, with only exposed children needing to recruit the left angular gyrus to a greater extent as number comparison task difficulty increased. Further, reduced activation of the right posterior superior parietal lobule in children with increasing prenatal alcohol exposure suggests that exposed children may be less able to employ the attentional systems associated with number processing. Notably, activation of nonsyndromal heavily exposed children was impaired in the right posterior superior parietal lobule, but spared in the right horizontal intraparietal sulcus. In boys only, prenatal alcohol exposure was associated with poorer place learning and reduced activation during place learning in the precuneus and posterior cingulate, as well as parahippocampal gyrus, frontal and temporal lobes, caudate, insula, claustrum, lentiform nucleus and thalamus. In girls, prenatal alcohol exposure was not associated with place learning performance or activation during place learning in any regions. These results confirm that boys and girls use different navigation strategies that rely on different brain regions and suggest that the regions used by boys are more susceptible to alcohol damage, while the regions used by girls are relatively spared. In conclusion, all the tasks investigated showed prenatal alcohol exposure related alterations in parietal function, with the impairments being widespread throughout the parietal lobe bilaterally. Notably, activation of the bilateral precuneus was affected by prenatal alcohol exposure in both the spatial navigation and nonsymbolic number comparison tasks. It is possible that this is a key region linking the deficits in number processing and visuospatial skills in children with prenatal alcohol exposure.